Hepatoprotective Effect and Molecular Mechanisms of Hengshun Aromatic Vinegar on Non-Alcoholic Fatty Liver Disease - Zhu, Shenghu; Guan, Linshu; Tan, Xuemei; Li, Guoquan; Sun, Changjie; Gao, Meng; Zhang, Bao; Xu, Lina (Frontiers in Pharmacology, 2020)
Aromatic vinegar with abundant bioactive components can be used as food additive to assist the treatment of various diseases. However, its effect on non-alcoholic fatty liver disease (NAFLD) is still unknown. The purpose of this study was to investigate the mechanism of Hengshun aromatic vinegar in preventing NAFLD in vivo and in vitro. Aromatic vinegar treatment was applied to rats fed with high-fat diet (HFD) and HepG2 cells challenged with palmitic acid (PA). Our results showed that aromatic vinegar markedly improved cell viabilities and attenuated cell damage in vitro. The levels of TC, TG, FFA, AST, ALT and malondialdehyde (MDA) in HFD-induced rats were significantly decreased by aromatic vinegar. Mechanism investigation revealed that aromatic vinegar markedly up-regulated the level of Sirt1, and thereby inhibited inflammation pathway through down-regulating the expressions of HMGB1, TLR4, NF-κB, TRAF6 and inflammatory factors. Aromatic vinegar simultaneously increased the expression of FXR and suppressed expressions of lipogenesis related proteins, including FASN, ACC1, SREBP1 and SCD. These results were further validated by knockdown of Sirt1 using siRNAs silencing in vitro. In conclusion, Hengshun aromatic vinegar showed protective effects against NAFLD by enhancing the activity of SIRT1 and thereby inhibiting lipogenesis and inflammation pathways, which is expected to become a new assistant strategy for NAFLD therapy in the future.